Dignity, Difference, and the Representation of Nature. (August 2021) - Dienstag, Joshua Foa
In the past few decades, political theorists have attempted to articulate a nontheological basis for a special human place in the moral universe. These attempts, I argue, generally fall into two groups, one centered around the concept of "dignity" and the other around ideas of "difference." Both of these attempts ultimately fail, I maintain, but their failures are instructive and help us along a path toward a better kind of relationship with nature and the earth as well as one another. In the face of increased scientific knowledge about the environment, animals, and our own species, we have every reason to recalibrate our stance toward nature as a whole. But in doing so we must acknowledge that the human relationship with nature is ultimately a representative one that can therefore never achieve the kind of reciprocity available in human society. Whatever form our respect for nature takes, it will always be distinct from the relationships we have with those we consider co-citizens.